Pengaruh Faktor Ekonomi Makro, Risiko Investasi, Kinerja Keuangan dan Struktur Kepemilikan terhadap Return Saham Perusahaan di BEI - Mirana Lavenia; Hwihanus Hwihanus (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This research aims to analyze the influence of macroeconomic factors, investment risk, financial performance, and ownership structure on company stock returns on the Indonesia Stock Exchange (BEI). Using a quantitative research design, primary and secondary data are used to investigate the relationship between these variables. Research results over the last three year period show that macroeconomic factors do not have a significant impact on stock returns, financial performance, investment risk, or ownership structure. On the other hand, financial performance has a positive and significant influence on stock returns and ownership structure, while investment risk has a positive and significant influence on stock returns and ownership structure. Ownership structure, although it has a negative effect on stock returns, has a relatively small effect. The suggestion from this research is the importance of a company's focus on internal factors such as financial performance and investment risk management to increase stock returns. Regular evaluation of the ownership structure is also recommended to ensure alignment with long-term business goals.